Printed document integrity verification using barcode - Husain, Affandi (Penerbit UTM Press, 2014)
Printed documents are still relevant in our daily life and information in it must be protected from threats and attacks such as forgery, falsification or unauthorized modification. Such threats make the document lose its integrity and authenticity. There are several techniques that have been proposed and used to ensure authenticity and originality of printed documents. But some of the techniques are not suitable for public use due to its complexity, hard to obtain special materials to secure the document and expensive. This paper discuss several techniques for printed document security such as watermarking and barcode as well as the usability of two dimensional barcode in document authentication and data compression with the barcode. A conceptual solution that are simple and efficient to secure the integrity and document sender's authenticity is proposed that uses two dimensional barcode to carry integrity and authenticity information in the document. The information stored in the barcode contains digital signature that provides sender's authenticity and hash value that can ensure the integrity of the printed document.